Perspektif Masa Depan Robotika Kolaboratif dalam Ekonomi Digital Berbasis 6G - Azzam al Alim; Gesita Fadya Yuyen; Irene Grace Evangelina; Kelvin Lie (Jurnal Ilmiah Sistem Informasi, 2025)
The rapid advancement of wireless communication technology has significantly influenced industrial automation, particularly in collaborative robotics (cobots). With the expected commercial deployment of 6G by 2030, this technology offers ultra-high-speed data transmission, low latency, and deep integration of Artificial Intelligence (AI). This study investigates the impact of 6G on enhancing the performance and efficiency of cobots in industrial settings, addressing challenges related to real-time coordination, network latency, and economic implications. The results indicate that cobots powered by 6G achieve a 25-30% increase in throughput, a latency reduction to 0.5 - 0.8 ms, and a 15-20% improvement in energy efficiency compared to 5G-based cobots. These enhancements facilitate more precise and adaptive human-robot interactions, improving operational flexibility and productivity across various sectors. However, challenges such as infrastructure readiness, cybersecurity risks, and high implementation costs remain key concerns. This study provides a comprehensive analysis of the synergy between 6G and collaborative robotics, offering valuable insights for industries preparing for next-generation automation.